Prisons of the Mind: Social Value and Economic Inefficiency in the Criminal Justice Response to Mental Illness - Pustlinik, Amanda C. (2005)
Can constructs of social meaning lead to actual criminal confinement? Can the intangible value ascribed to the maintenance of certain social norms lead to radically inefficient choices about resource allocation? The disproportionate criminal confinement of people with severe mental illnesses relative to non-mentally ill individuals suggests that social meanings related to mental illness can create legal and physical walls around this disfavored group. Responding to the non-violent mentally ill principally through the criminal system imposes at least 6 billion dollars in costs annually on the public, above any offsetting public safety and deterrence benefits, and imposes terrible human costs on people who suffer from these illnesses. Yet, the criminal confinement regime may create intangible social value by reinforcing norms related to personal responsibility, based on the current and historical social meaning of mental illness. And social meaning, according to legal scholars working in expressive or New Chicago School law and economics, is an essential term in the economic analysis of law. Reform efforts aimed at replacing the current punitive paradigm with a medical or therapeutic model founder because they fail to account for the social meanings that maintain the punitive paradigm and for the social value it creates. Understanding the social meanings of mental illness and how they intersect with the norm-enforcing role of the criminal law can lead to normatively literate reform proposals, liberating tremendous economic and human value. Those who seek to improve the conditions of this group, or liberate economic value, or both, must work to supplant what may be termed the moral/punitive paradigm of mental illness with a medical/therapeutic paradigm. In tandem, proposed policies relating to this - or any - disfavored group must be framed in ways that do not conflict with the views and values of the majority whose support must be achieved